2019
DOI: 10.2217/pgs-2019-0063
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variants in Members of the Krüppel-Like Factor Gene Family are Associated with Disease Severity and Hydroxyurea Treatment Efficacy in β-Hemoglobinopathies Patients

Abstract: Aim: β-Type hemoglobinopathies are characterized by vast phenotypic diversity as far as disease severity is concerned, while differences have also been observed in hydroxyurea (HU) treatment efficacy. These differences are partly attributed to the residual expression of fetal hemoglobin (HbF) in adulthood. The Krüppel-like family of transcription factors (KLFs) are a set of zinc finger DNA-binding proteins which play a major role in HbF regulation. Here, we explored the possible association of variants in KLF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Kru ¨ppel-like family is a group of zincfinger transcription factors which play key regulatory roles in cellular growth, development, differentiation and vascularization. [28][29][30] A study of transcriptome changes after oxygen-glucose deprivation showed that KLF10 was upregulated in rat aortic smooth muscle cells cultured under ischemic conditions, and transfection of hypoxia-inducible factor-1a siRNA reduced the hypoxia-induced increase in KLF10 mRNA. 31 Although there is not much research on the regulation mechanism of KLF10 in ischemia reperfusion, there are many evidences that Kru ¨ppel-like family members play an important biological role in the process of ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Kru ¨ppel-like family is a group of zincfinger transcription factors which play key regulatory roles in cellular growth, development, differentiation and vascularization. [28][29][30] A study of transcriptome changes after oxygen-glucose deprivation showed that KLF10 was upregulated in rat aortic smooth muscle cells cultured under ischemic conditions, and transfection of hypoxia-inducible factor-1a siRNA reduced the hypoxia-induced increase in KLF10 mRNA. 31 Although there is not much research on the regulation mechanism of KLF10 in ischemia reperfusion, there are many evidences that Kru ¨ppel-like family members play an important biological role in the process of ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%